Bosutinib-related pneumonitis. Issue 3 (12th September 2017) - Jutant, Etienne-Marie; Meignin, Véronique; Montani, David; Tazi, Abdellatif; Rousselot, Philippe; Bergeron, Anne
We read with interest the recent correspondences from Hickey et al . [1] and Riou et al . [2] reporting bosutinib-associated pulmonary arterial hypertension (PAH) and pleural effusion. Tyrosine kinase inhibitors (TKIs) have revolutionised the treatment of chronic myeloid leukaemia (CML). However, TKIs are associated with potentially serious lung complications, which are particularly associated with dasatinib; the incidence of dasatinib-induced pleural effusion ranges from 15% to 35% [3, 4]. Dasatinib-related PAH has been reported in ∼0.45% of dasatinib-treated patients [5]. Bosutinib (developed by Pfizer (New York, NY, USA) in 2015) is a second-generation TKI approved for patients with CML that is resistant or intolerant to imatinib, nilotinib or dasatinib [6]. Bosutinib can induce parenchymal, pleural and vascular lung disease http://ow.ly/qMiQ30dMVK5